2020
DOI: 10.25259/cjhs_13_2019
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic effect of N-acetylcysteine against dexamethasone-induced hyperlipidemia in rats

Abstract: Objective: The liver is a key metabolic organ involved in lipid metabolism and maintenance of cholesterol homeostasis in the body. However, hypercholesterolemia and oxidative stress is associated with the fatty liver which is the major risk factor associated with cardiovascular diseases (CVDs). The objective of this study was to investigate the hypolipidemic property of N-acetylcysteine (NAC) in dexamethasone-induced hyperlipidemic rats. Materials and Methods: Dexamethasone (10 mg/kg) was administered on alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…It was observed that the administration of A. conyzoides upturned the enhanced lipid peroxidation and the consequent decline in the level of enzymatic antioxidant (GPx, SOD, and CAT) as well as the activities of nonenzymatic antioxidant (MDA) in the cardiac tissue of diabetic rats. Our finding is in accordance with the reports of [ 6 , 28 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It was observed that the administration of A. conyzoides upturned the enhanced lipid peroxidation and the consequent decline in the level of enzymatic antioxidant (GPx, SOD, and CAT) as well as the activities of nonenzymatic antioxidant (MDA) in the cardiac tissue of diabetic rats. Our finding is in accordance with the reports of [ 6 , 28 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, the extract suppresses ALX's cytotoxic action by causing the regeneration of the myocardium, which restores myocardial tissues and increases the heart's interstitium space, which was observed in the histoarchitectural analysis ( Figure 5(c) and Figure 5(d) ). Appraisal of SOD, CAT, GPx, lipid peroxidation, and other antioxidant enzyme activities in biologicaltissue has always been used as markers for oxidative stress [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trace elements Copper and Zinc varied in content in the juice within much narrower limits while Potassium was found to be higher. High amount of potassium in the body was reported to increase iron utilization (Mada et al, 2014), and it is beneficial to people taking diuretics to control hypertension and suffering from excessive excretion of potassium through the body fluid (Arinathan et al, 2003). The levels of Manganese, Potassium and magnesium were found to be high in the juice, which is similar to the findings of (Olununmi et al, 2013).…”
Section: Phytochemical Screening Resultssupporting
confidence: 80%
“…Oxidative stress was induced by intraperitoneal administration of 150 mg/kg body weight of CCl4 to the Wistar albino rats. Liver diseases are mostly mediated by reactive oxygen species (ROS) which play a significant role in the development of tissue injury and pathological conditions in the living system (Mada et al, 2014). In the current study, it was observed that there was decrease in the level of oxidative stress markers in the CCl4-induced oxidative stress control rats.…”
Section: Phytochemical Screening Resultsmentioning
confidence: 55%
“…36 This result revealed that NAC showed lipid-lowering effect, which was consistent with previous report. 37,38 The change in lipid profile, including TCh, TG, HDL, LDL, and atherogenic index indicated that NAC could effectively attenuate hyperlipidemia in GDM mice, which suggested that reducing hyperlipidemia by NAC might also contribute to the treatment of GDM.…”
Section: Discussionmentioning
confidence: 98%